Older Lifelong Learners' Motivations for Participating in Formal Volunteer Activities in Urban Communities. (May 2017) - Yamashita, Takashi; López, Erick B.; Soligo, Marta; Keene, Jennifer R.
In recent years, volunteering has received increasing attention as a unique form of learning, one which may complement lifelong learning programs for older adults. This study examined the underlying volunteer motivations as well as formal volunteer behaviors among older adult lifelong learners. Data from 277 members of the Osher Lifelong Learning Institute in an urban community in the western part of the United States were analyzed using exploratory factor analysis and binary logistic regression models. Results showed that generativity (i.e., a desire to help next generations or communities), personal development, and well-being are salient underlying volunteer motivators. However, only generativity was associated with actual volunteering among older lifelong learners (odds ratio = 1.55; standard error = .17; p < .05). These findings suggested that existing lifelong learning programs might consider incorporating volunteer-based service learning components into their curricula in order to further promote the benefits of lifelong learning among older adults.